Secondary school ESL teachers’ beliefs and practices in the teaching of pronunciation / Shanina Sharatol Ahmad Shah - Ahmad Shah, Shanina Sharatol (2014)

(untitled)
Despite the emphasis on the role of pronunciation in obtaining proficiency in the English Language and the rightful place it has been given in the Malaysian Secondary School English Language syllabus, pronunciation still struggles to gain the attention it deserves in the ESL classrooms. Thus, it is the purpose of this study to investigate the beliefs of selected ESL teachers that have led to their decisions on their classroom practices in pronunciation instruction. This study focuses on three aspects of the teachers’ beliefs; firstly, the beliefs of their roles in learning and teaching pronunciation. Secondly, the beliefs they hold about the focus areas in pronunciation instruction and finally, their beliefs of approaches in the teaching of pronunciation. This study also investigates the ESL teachers’ strategies in incorporating the instruction of pronunciation features in their teaching of other language skills and contents. Then, the congruence of the teachers’ beliefs about pronunciation instruction and their classroom instructional practices are looked at to understand the process that happens between them. The study utilizes a multiple case study approach which allows an in-depth investigation that captures the actual beliefs and practices of five selected secondary school ESL teachers in pronunciation instruction. A multiple case study was employed as it could help to unravel the complexity of beliefs in a curricular area which is often left out from the ESL lessons. The teachers were purposively selected to have an array of different educational background as well as professional experience. The data was collected from in-depth interviews with the participants and selected students taught by these participants. Besides interviews, data was also collected from observations of their selected ESL lessons to observe the practices of the integration of pronunciation into the ESL lessons. The data was then analysed manually to get the feel of the data. The triangulation of this study is enhanced through the cross case analysis of the data and the various methods of data collection. The study has found that the five teachers had vague and negative beliefs about pronunciation instruction. Most of the beliefs on pronunciation instruction they had were the reflections of their unsupportive experience during their schooling and professional experience. The ESL teachers’ current teaching situations with the examination requirements and packed schools’ agendas that limited their time to include the teaching of pronunciation contributed to their negative beliefs about pronunciation instruction. This is evident in their practices of pronunciation in the ESL classrooms observed. The contextual factors that bound the teachers and their teaching practices have a large impact on their decisions of whether to regard or disregard pronunciation in their ESL lessons. This study has concluded that conflicts occur between the English Language curriculum and the implementation of pronunciation instruction. As a result, teaching pronunciation appears to be challenging to the ESL teachers. This is supported by the trivialization of the pronunciation component by many parties including the participants themselves. The negative congruence between the teachers’ beliefs about pronunciation instruction and their practices would indicate serious implications in the future of ESL instructions.